Influence of the use of acclimatized inoculum in the composting process - Morais, Carlos Alberto Silvestre [UNESP]; Fiore, Fabiana Alves [UNESP]; Esposito, Elisa (FapUNIFESP (SciELO), 2022)
The composting of the organic fraction of urban solid waste is one of the treatments considered as adequate in Brazil, but whose adoption is insignificant. The search for solutions that enable the use of the process as an agent for the reintegration of organic matter in the production cycle is the guiding principle of this work, which aimed to perform an exploratory assessment of the consequences, for the composting process and products, of the addition of inoculants with acclimatized microorganisms. The experiment was carried out with the use of organic residues and leaves that were composted in two reactors with active aeration, without mixture, and one of them received the addition of acclimatized inoculant in the region of the study. The physical-chemical and microbial characteristics of the residues were evaluated, the pH and temperature parameters were monitored during composting and the quality of the resulting materials was evaluated. The results showed that the use of acclimatized inoculants ensured greater efficiency in the chemical transformation of organic material, favored the germination and growth of seeds by diluted leachate, and produced compost with greater aptitudes for soil conditioning. From the real-time monitoring of the temperature, it was also possible to verify that the batch aeration can have a negative influence on the microbial community during the composting process. The continuity of composting studies with the use of acclimated inoculants is recommended, since it can positively contribute to the aggregation of macronutrients and microbial communities in the areas of application of the compound and leachate.
Influência do uso de inóculo aclimatado em processo de compostagem
Keywords: efficient microorganisms; inoculants; organic waste; urban solid waste